Cognitive control in honesty and dishonesty under different conflict scenarios: insights from reaction time - Li, Hao-Ming; Yan, Wen-Jing; Wu, Yu-Wei; Huang, Zi-Ye (Frontiers in Psychology, 2024)
This study investigated the role of cognitive control in moral decision-making, focusing on conflicts between financial temptations and the integrity of honesty. We employed a perceptual task by asking participants to identify which side of the diagonal contained more red dots within a square to provoke both honest and dishonest behaviors, tracking their reaction times (RTs). Participants encountered situations with no conflict, ambiguous conflict, and clear conflict. Their behaviors in the clear conflict condition categorized them as either “honest” or “dishonest.” Our findings suggested that, in ambiguous conflict situations, honest individuals had significantly longer RTs and fewer self-interest responses than their dishonest counterparts, suggesting a greater need for cognitive control to resolve conflicts and a lesser tendency toward self-interest. Moreover, a negative correlation was found between participants’ number of self-interest responses and RTs in ambiguous conflict situations (r = −0.27 in study 1 and r = −0.66 in study 2), and a positive correlation with cheating numbers in clear conflict situations (r = 0.36 in study 1 and r = 0.82 in study 2). This suggests less cognitive control was required for self-interest and cheating responses, bolstering the “Will” hypothesis. We also found that a person’s self-interest tendency could predict their dishonest behavior. These insights extend our understanding of the role of cognitive control plays in honesty and dishonesty, with potential applications in education, policy-making, and business ethics.